Gut microbiota characterization in Egyptian patients with hepatocellular carcinoma post-chronic hepatitis C virus genotype 4 infection - Karim Montasser, Heba Ahmed Osman, Hanan Abozaid, Mohammed H. Hassan, Abeer M. M. sabry (Journal of Applied Pharmaceutical Science, 2021)
This study aimed to evaluate the possible role of gut dysbiosis in the development of hepatocellular carcinoma (HCC) in patients with chronic hepatitis C virus (HCV) infection. This study was carried out on 400 individuals categorized into three groups: group I included 100 patients with HCC; group II included 200 chronic HCV-infected patients; and group III included 100 healthy control subjects. The included patients were evaluated using Child–Pugh, tumor (T), nodes (N), and metastases (M) (TNM), and Barcelona Clinic Liver Cancer (BCLC) scoring systems. In addition to routine investigations (complete blood counts, complete liver function tests, international normalized ratio, HCV antibodies, and hepatitis B surface antigen), polymerase chain reaction of stool microbiota, HCV infection, and alphafetoprotein were assessed for all patients. The results revealed no significant difference between HCC patients and control patients (p > 0.05) regarding Bacteroides fragilis and Akkermansia muciniphila. Faecalibacterium prausnitzii and Bifidobacterium were detected in fewer patients with HCC (51% and 43%, resp.) compared with healthy controls (70% and 76%, resp.) (p < 0.05). Lactobacillus and Escherichia coli were detected in more patients with HCC (80% and 81%, resp.) compared with healthy controls (36% and 58%, resp.), p < 0.001. No significant differences were detected between gut microbiota and HCC progression with respect to Child–Pugh or TNM scores. However, B. fragilis was detected in stool isolates from 66.7% of BCLC stage IV patients compared with 10.7% of BCLC stage I patients. Thus, characteristic patterns of Bifidobacterium, Lactobacillus, and E. coli species in patients with chronic HCV and HCC were detected. Therapies targeting altered gut microbiota may be beneficial in reducing the risk of HCC in patients with HCV infection, as altered gut microbiota is a predisposing factor for liver disease progression.
Keywords: HCV, hepatocellular carcinoma, Gut microbiota, Enterobacteriaceae, Lactobacillus, polymerase chain reaction